Two new species of Perlidae (Plecoptera) from Mato Grosso State, western Brazil - Bispo, Pitágoras da Conceição [UNESP]; Neves, Cláudio O.; Froehlich, Claudio G. (My University, 2005)
Adult stoneflies collected in emergence and light traps in central Mato Grosso State are studied. Two new species, Anacroneuria jaciara sp.n. and Macrogynoplax matogrossensis sp.n. are described. Copyright © 2005 Magnolia Press.
Keywords: Anacroneuria; Brazil; Macrogynoplax; Mato Grosso; Perlidae; Plecoptera